2006
DOI: 10.1038/nsmb1062
|View full text |Cite
|
Sign up to set email alerts
|

Active PHO5 chromatin encompasses variable numbers of nucleosomes at individual promoters

Abstract: Transcriptional activation is often associated with chromatin remodeling. However, little is known about the dynamics of remodeling of nucleosome arrays in vivo. Upon induction of Saccharomyces cerevisiae PHO5, a novel kinetic assay of DNA methyltransferase accessibility showed that nucleosomes adjacent to the histone-free upstream activating sequence (UASp1) are disrupted earlier and at higher frequency in the cell population than are those more distal. Individually cloned molecules, each representing the chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
46
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 48 publications
10
46
0
Order By: Relevance
“…31 and Fig. S4), and the nucleosomes of this gene were shown to undergo significant rearrangement upon phosphate starvation, as determined by electron microscopy (30) and methyltransferase accessibility (34). In agreement with previous studies (35,43,44), PCR-based nucleosome-scanning assay showed marked shifts in chromatin structure (Fig.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…31 and Fig. S4), and the nucleosomes of this gene were shown to undergo significant rearrangement upon phosphate starvation, as determined by electron microscopy (30) and methyltransferase accessibility (34). In agreement with previous studies (35,43,44), PCR-based nucleosome-scanning assay showed marked shifts in chromatin structure (Fig.…”
Section: Resultssupporting
confidence: 76%
“…1B) and genome-wide micrococcal nuclease (MNaseseq) were performed (Fig. 1C), confirming previously reported nucleosome positioning on the PHO5 promoter for positions of the +1 through −3 nucleosomes of the PHO5 promoter under phosphate-rich conditions, which is nonpermissive for gene expression (30,(32)(33)(34)(35).…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations